P Karakter Topeng Manis Sebagai Inspirasi Penciptaan Produk Kriya Kebutuhan Ruang Pertemuan Formal - I Wayan Wijaya Kusuma; I Made Gede Arimbawa; I Made Sumantra (Hastagina : Jurnal Kriya Seni, 2021)
Mask are one of the cultural heritages of people in various part of the world who have a mask culture that use different methods and functions according to local custom. In society, various mask are used, such as being used to support a scared belief or spirituality and used as a support for a theatrical performance as well as commodity goods that are profane. Like wish, there are various types of mask with various characters. Such as hard characters of fierce, sweet, cute and so on, this condition is very interesting to be explore and used as a source of inspiration in the creation of craft products. Condisering the mask that are starting to get less attention by the younger generation at this time so that these mask are not eroded by the current technology, in addition, he also wants to preserve the existence of mask so that in the future that arts will be more awake than these mask. This became the basic idea in creating works for the needs of formal meeting room that apply topeng manis as decorations. The creation process has gone through various stages which can describe an ordely and well structured creation process. That are three stage that are carried out, namely : 1. Exploration here is through the exploration stage to find ideas, observations, interviews, surveys, data colletion and references that will be used as the basis for designing or making desaign; 2. The desaign is made from the result of data acquisition and is formulated in a single unit in the form of a sketch; 3. The embodiment is carried out from the result of the selected sketches and will be transferred to the media so that works that have gone through various processes and techniques such as assembly formation and finishing are realized The creation of this works is used as a product for the needs of a formal meeting room by applying a topeng manis as the creation of the works. Meeting room as a place to accommodate meeting activities that discuss general problems or inspiration about something interesting.